MOTIVASI DALAM PEMBELAJARAN BAHASA INGGRIS: STUDI KASUS PADA MAHASISWA SASTRA INGGRIS UNISMA - Heri Yusuf (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2012)
This research reports the orientations that become the foundations of students’ motivation in learning English and their attitude towards courses and their instructors. The method used is a survey by randomly asking the students in English Department of UNISMA Bekasi to fill out a questionnaire adapted from Attitude Motivation Test Battery (AMTB) designed by R.C. Gardner. The purpose of the research is to uncover the students’ orientations in learning English and to see their attitude towards courses and their instructors. The result shows that out of 68 returned questionnaires, 60 students appear to have not only integrative but also instrumental orientations. 47 students responded positively towards course instructors and nine of them responded negatively. As for the attitude towards courses, 39 students show positive response, while 17 of them seem to have negative one